Peran Sistem Informasi Manajemen Dalam Mendorong Keberlanjutan Operasional Perusahaan - Pratama, Arya Yudi; Nasution, Muhammad Irwan Padli (CV. SINAR HOWUHOWU, 2026)
This This study aims to examine the role of Management Information Systems (MIS) in supporting the operational sustainability of companies through enhanced efficiency, data-driven decision- making, and the application of corporate social responsibility principles. The optimal implementation of MIS enables companies to manage information in an integrated manner, utilize resources effectively, and adopt business practices aligned with sustainability principles. This research employs a descriptive literature study method by reviewing previous studies that focus on operational efficiency, sustainability reporting, and information-based corporate governance. The findings indicate that the integrated application of MIS can accelerate workflows, reduce operational costs, increase transparency, and strengthen the company’s commitment to achieving the Sustainable Development Goals (SDGs). Furthermore, MIS serves as a strategic instrument that assists companies in adapting to technological advancements, improving accountability, and building competitiveness in the digital era. Therefore, effective MIS implementation contributes significantly to achieving efficient, sustainable, and future-oriented corporate operation.